Middle class vulnerability to covid-19 pandemic effects and government measures in Metropolitan Lima - Bürkli Bürkli, Hans Adrian; Hernández Garavito, Jorge; Mendoza García, Diego Alberto; Riva Zaferson, Franco Alberto (Pontificia Universidad Católica del Perú, 2021)
Using National Household Survey data, this study examines the situation of Peruvian middle class households in Metropolitan Lima and Callao prior to the COVID-19 pandemic through financial and non-financial variables in order to identify vulnerability factors in the overall population and in income quintiles. The analysis has revealed that health, income and labor are the most vulnerable indicators and could be heavily affected by government measures against COVID-19, such as mandatory social isolation (lockdown), social distancing, and movement and gathering restrictions. In this context, households in the lowest quintile are substantially more susceptible to falling into poverty due to economic instability, labor informality and lack of social protection. The study results suggest that the definition of “vulnerability” needs to go beyond poverty measurements to improve the focalization of government policies and strategies in similar crises.

Utilizando los datos de la encuesta nacional de hogares, el estudio examina la situación previa a la pandemia causada por la COVID-19 de los hogares peruanos de clase media en Lima Metropolitana y Callao, a través de variables financieras y no financieras, para identificar factores de vulnerabilidad a nivel general y en grupos basados por quintiles del nivel de ingresos. El análisis encontró mayor vulnerabilidad en los indicadores vinculados a salud, ingresos y empleo, los cuales pueden verse gravemente afectados por las medidas del gobierno ante la COVID-19 como el aislamiento social obligatorio (cuarentena), el distanciamiento social y las restricciones en la libertad de movilización y reunión. En este contexto, los hogares del quintil más pobre se encuentran sustancialmente más vulnerables a caer en pobreza debido a la inestabilidad económica, el empleo informal y la falta de protección social. Los resultados sugieren que la definición de vulnerabilidad debe expandirse más allá de las medidas de pobreza para mejorar la focalización de las políticas y estrategias del gobierno en crisis similares.
Middle class vulnerability to covid-19 pandemic effects and government measures in Metropolitan Lima
Keywords: COVID-19; https://purl.org/pe-repo/ocde/ford#5.02.04